Factores de mediación docente en la comunicación oral en inglés en estudiantes del quinto grado de secundaria en instituciones educativas del distrito de Iquitos 2020 - Gonzales Pezo, Susybel Mercedes (2021)
The main objective of this study was to explain the influence of teacher mediation factors in fifth year students’ oral communication skills at Iquitos district secondary schools in 2020. The research type was explicative with field study, transectional contemporary and multivariate designs. The population consisted of 2,546 students with a random stratified sample of 116 with proportional affixation. The data gathering tools were a valid and reliable listening test, speaking performance test, rubrics and questionnaire. The results of the study show that the teacher’s mediation factors mean score was 35,92 and the mean score of oral communication was 5,71, while the Rho in the variables was ,051 evidencing a very low correlation. As no correlation existed, the binary logistic regression analysis was not carried out. Consequently, there is no influence of teacher mediation in the study population students’ oral communication in English.